Law No 77/2016 On Amending Certain Provision of Law No. 89 of the year 1960 Concerning the Entry and Residence of Foreigners in, and their Exit From, the Territories of the Arab Republic of Egypt = قانون رقم 77 لسنة 2016 بتعديل بعض أحكام القانون رقم 89 لسنة 1960 في شأن دخول وإقامة الأجانب بأراضي جمهورية مصر العربية والخروج منها / Prime Minister - Egypt. Prime Minister (2025)
Law no. 77 of the year 2016 on amending certain provisions of law no. 89 of the year 1960 concerning the entry and residence of foreigners in, and their exit from, the territories of the Arab republic of Egypt قانون رقم 77 لسنة 2016 بتعديل بعض أحكام القانون رقم 89 لسنة 1960 فى شأن دخول واقامة الأجانب بأراضى جمهورية مصر العربية والخروج منها